1978
DOI: 10.1021/bi00616a002
|View full text |Cite
|
Sign up to set email alerts
|

Ethidium bromide complexes with self-complementary deoxytetranucleotides. Demonstration and discussion of sequence preferences in the intercalative binding of ethidium bromide

Abstract: The binding of ethidium bromide to the self-complementary deoxytetranucleotides containing guanine and cytosine bases has been studied by circular dichroism, visible absorption, and fluorescence spectroscopies. The circular dichroism spectrum of each of the four deoxytetranucleotides was measured and compared to the spectrum calculated by a nearest-neighbor approximation method which utilized the circular dichroism spectra of the deoxydinucleotides as a basis set. Reasonable agreement was obtained between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 22 publications
3
34
0
1
Order By: Relevance
“…The rigidity of the chain prevents occupancy of two adjacent binding sites by rings belonging to the same dimer; then only the noncontiguous CpG sites are filled in a bisintercalated d(CpGpCpG)2-Ditercalinium complex. Such a model agrees with the classical pyrimidine-purine sequence preference displayed by intercalators (9,21) and with the similar upfield shifts induced on both the internal and the external base pair protons.…”
Section: Methodssupporting
confidence: 86%
“…The rigidity of the chain prevents occupancy of two adjacent binding sites by rings belonging to the same dimer; then only the noncontiguous CpG sites are filled in a bisintercalated d(CpGpCpG)2-Ditercalinium complex. Such a model agrees with the classical pyrimidine-purine sequence preference displayed by intercalators (9,21) and with the similar upfield shifts induced on both the internal and the external base pair protons.…”
Section: Methodssupporting
confidence: 86%
“…It is possible that their accompanying diastereomers are present as minor uncharacterized products in our chromatographic system. Also, a .. MOP.-F41 may consist of more than a single diastereomer, but complete Such short range sequence specificity has been observed with other intercalating agents such.as ethidium bromide (Kastrup et al, 1978).…”
Section: Analysis By Fdms Gave Identical Results For 8-mop Fractions F38mentioning
confidence: 88%
“…Although it has been established that ethidium has a preference for binding to pyrimidine(3'-5') purine sequences when compared to purine(3'-5')pyrimidine sequences (9)(10) it has also been shown that the apparent binding affinity of ethidium is not very dependent upon the overall base composition (1-2, 13). The equilibrium binding of ethidium to various native DNAs has been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), with the binding isotherms presented in these papers being well represented by the nearest neighbor exclusion model (14)(15) Volume 10 Number 24 1982 and Young (16) which showed that daunorubicin and adriamycin facilitated the binding of actinomycin D to poly(dA-dT). poly(dA-dT), a polynucleotide to which actinomycin D does not bind.…”
Section: Introductionmentioning
confidence: 99%